Scabiosis, Otitis Externa, With Toxocariosis and Ancylostomiasis In Local Cat - Muhammad Hasby Arrizki Akbar; Putu Ayu Sisyawati Putriningsih; Sri Kayati Widyastuti (Universitas Airlangga, 2025)
Background: Skin diseases caused by ectoparasites are common health issues found in clinical cases involving domestic animals kept as pets. Scabiosis is a skin disease in livestock and companion animals caused by the Sarcoptes scabiei or Notoedres cati mites in the stratum corneum of the skin. Otitis externa is an inflammatory condition in the external ear canal. Toxocariosis is a disease brought on by parasites from the genus Toxocara. Hookworm disease is an infection by hookworms, Ancylostoma sp. Purpose: To report the management of scabiosis, otitis externa, toxocariosis and ancylostomiasis in local cats. Case: The case animal was a male cat named Chipmunk, aged 3 years, with orange eyes and hair color, 2.4 kg body weight. The cat was examined due to redness on the back of the neck and scratching behavior while eating. Upon physical examination, the cat appeared active and behaved calmly with a scratching habit. The pruritus score was 8/10. The Body Condition Score (BCS) was 3 out of 9. There was alopecia and hyperkeratosis on the face, ears, and neck; crusts on the neck area and scales on the face and neck. The nasal mucosa was moist and the oral mucosa was pale pink. Abdominal palpation revealed a relatively firm consistency. Laboratory examinations conducted included complete blood count (CBC), superficial skin scraping, ear cerumen swab, direct microscopic examination, sedimentation, floatation, and egg per gram for feces. Case Management: The treatment involved the administration of ivermectin and diphenhydramine injections, drontal, and prescribed medications included chlorpheneramine maleate, multivitamin, and fish oil. Conclusion: Treatment for scabiosis and otitis externa proved effective, as well as toxocariosis and ancylostomiasis clinically.